Effects of DL-ethionine on mouse liver tRNA base composition. - Lu, L W (1976)
Treatment of mice with DL-ethionine and adenine causes a reduction of all methylated bases of liver tRNA. This effect is dose-dependent and specific for the methylated bases. Individual methylated components are affected to different extents, m22G being most sensitive to inhibition.